Dominican Mission in the Baltic Sea Region With Comparative Looks to Mendicant Mission on the Entire East-European Frontier - Gøgsig Jakobsen, Johnny Grandjean 1968- (2018)
A traditional view of the Dominican Order as deeply involved with mission to the non-Catholic peoples of medieval Europe - Muslims, Jews, Orthodox Christians, and pagans alike - has recently been challenged by studies of Robin Vose and others. Organized Dominican activities in most border zone-regions with mixed religions almost exclusively appear to have been aimed at Catholic minorities, whereas actual proselytizing efforts towards non-Catholics was mainly an issue for a few individual, particularly devoted friars. The present article argues, however, that this general picture may differ when looking at Dominican contacts with pagan peoples on the north-eastern and northern borders of Western Christianity, where evidence does point to a more organized mission that was actually implemented.